Groupes algériques semi-simples en dimension cohomologique <̲ 2 = Semisimple algebraic groups in cohomological dimension <̲ 2 /: Semisimple algebraic groups in cohomological dimension <̲ 2. ([2019]) - Gille, Philippe, 1968-
No abstract available